Efficacy and safety of PD-1 inhibitors plus anti-angiogenesis tyrosine kinase inhibitors with or without transarterial chemo(embolization) for unresectable hepatocellular carcinoma: a meta-analysis - Chen, Yue; Jia, Luyao; Li, Yu; Cui, Wenhao; Wang, Jukun; Zhang, Chao; Bian, Chunjing; Luo, Tao (Frontiers in Oncology, 2024)
Background The triple combination of programmed cell death protein–1 (PD-1) inhibitors plus anti-angiogenesis tyrosine kinase inhibitors (TKIs) with or without transarterial chemoembolization (TACE) or hepatic arterial infusion chemotherapy (HAIC) enhance the effect of treatment for unresectable hepatocellular carcinoma (uHCC). The present study compared the efficacy and safety of PD-1 plus TKI with or without transarterial chemo(embolization) for uHCC. Methods The meta-analysis was conducted using data acquired from PubMed, EMBASE, the Cochrane Library, Ovid, Web of Science, and Clinical Trials.gov from the inception date to December 2023. All clinical outcomes of interest included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs). The hazard ratio (HR) and risk ratio (RR) with 95% confidence intervals (CIs) were used to measure the pooled effect. In addition, subgroup analysis was conducted to determine the specific patient population that benefited. Results The OS (HR = 0.47; 95% CI: 0.39–0.56, P < 0.05), PFS (HR = 0.52; 95% CI: 0.45–0.60, P < 0.05), and ORR (RR = 1.94; 95% CI: 1.60–2.35, P < 0.05) were significantly better in TACE/HAIC+TKI+PD-1(TACE/HAIC TP) group than TKI+PD-1(TP) group. The incidence of AEs was acceptable. Conclusion The triple therapy of TACE/HAIC TP had better efficacy for uHCC than TP, with acceptable security. Systematic review registration PROSPERO, identifier CRD42023475953.